Separation of PCBs by liquid chromatography on reversed phase sub-2-micron particle columns - Olsovská, Jana; Kresinová, Zdena; Flieger, Miroslav; Cajthaml, Tomás (Talanta, 2010)
A new ultra high-performance liquid chromatography method with UV detection was examined for detection and separation of polychlorinated biphenyls. This included optimization of separation conditions for two model mixtures containing seven and fifteen most relevant congeners, comparison of three types of reversed phase sub-2-micron particle sized columns and assessment of system suitability under the optimized conditions. Calibration curves determined in the range from 0.5 to 50.0 microg/mL exhibited correlation coefficients ranging from 0.997 to 0.999. Lower limits of detection ranged from 0.1 to 0.5 ppm. The most efficient Grace C18 column filled with 1.5 microm particles was then tested to separate the complex commercial mixture Delor 103, where the elution order was confirmed by GC-MS. 13 individual congeners were separated and some of the other co-eluting congeners could be resolved using another separation dimension performed with a mass spectrometry detector. The developed method could be directly applied to the separation of less complex mixtures in aqueous sample matrixes, which are used in general for enzyme degradation studies.
Keywords: Polychlorinated Biphenyls; Limit of Detection; limita detekce; Chromatography, High Pressure Liquid; Gas Chromatography-Mass Spectrometry; Calibration; kalibrace; vysokoúčinná kapalinová chromatografie; plynová chromatografie s hmotnostně spektrometrickou detekcí; polychlorované bifenyly